Impacto do investimento em máquinas e equipamentos sobre a inovaç\~ao tecnológica e a produtividade das firmas industriais Brasileiras - Patrick Franco Alves; Nayara Lopes Gomes; Eric Jardim Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– In developing economies the purchase of a new machine by the firm can be a way of introducing a new product or processes. Under such considerations, this paper searches to measure the assumption of innovation via machine embodied technology, by verifying its impacts over the firm's productivity. In order to control for possible simultaneity and self-selection relationship between the variables a structured system of equations is estimated. The found results reveal the existence of positive and statistically significant impacts from the investments decision on technological innovation over the firm's productivity. The treatment effect estimated for product and process innovation presents positive and significant impact over the labor productivity. The firm size seems to be an important role in shaping the invest decision, the investment intensity choice and the different forms of technological innovation.
Keywords: L60; D24; O32; 330; average treatment effect; investment in machines; technological innovation